CSC790: Search Engine and Web Navigation / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (Universiti Teknologi MARA (UiTM), 2020)
This course will introduce students to the principles of search and navigation technologies, ways of modelling different aspects of Web and how the Web is evolving. Student will learn how to deals with web search engines and explore the tools and techniques for effective web navigation. Student also will understand the concept of current technologies in the search and navigation context such as the mobile web and social networks.